Awareness and Stigma Toward Visible and Invisible Disabilities in Banda Aceh, Indonesia: A Sociological and Policy Analysis - Cut Nyak Salsabila; Niswah As Sayuthi; Athaya Rumaisha (Graha Primera Saintifika, 2025)
Public understanding of disability in Banda Aceh continues to rely heavily on visible physical markers, resulting in limited recognition of invisible disabilities. This study examines public awareness, stigma, and institutional readiness using a qualitative sociological approach supported by descriptive survey data. A total of 50 respondents completed online/offline surveys, complemented by semi-structured interviews with policymakers, educators, and community actors, as well as policy document review and limited observations. Findings show a sharp awareness gap: while most respondents (94%) were familiar with disability in general, only 22% recognized that disabilities can be non-visible. Neurodiverse behaviours were frequently interpreted as issues of discipline, parenting, or spiritual disturbance rather than developmental differences, reflecting culturally rooted stigma. Institutional readiness was also low. Only 20% perceived public services as inclusive, and just 18% believed frontline staff understood invisible disabilities. Interviews revealed that although Qanun Aceh No. 2/2025 provides a legal foundation, it lacks operational guidelines and disability-disaggregated data, limiting effective implementation. Overall, the study identifies substantial gaps in public understanding, persistent stigma, and inadequate institutional preparedness. Improved disability literacy, clearer regulations, and strengthened cross-sector capacity are essential to advancing inclusion for individuals with invisible disabilities in Banda Aceh.